WORLD ECONOMY FROM GEOGRAPHIC, ECONOMIC AND POLITICAL POINT OF VIEW - V. A. Gorbanyov (Vestnik MGIMO-Universiteta, 2018)
Book Review: Geography of world economy: traditions, modernity, prospects (in Russian) / Ed. By V.A.Kolosov & N.A.Sluka. Collective monograph. Moscow-Smolensk: Oikumena, 2016. 400 p.The book under review is a solid monograph, the result of the work of the famous geographers, whose core is staff and graduates of the World Economy Geography Department of the Geographic Faculty of the Moscow State University. The stages of formation and achievements of the national school of the world economy geographical research are revealed. Modern changes in the geography of material and non-material spheres are estimated. The changes in the place of countries and regions in the world economy and politics are considered. The international migration of the population at different territorial levels has been analyzed. It seems that the book under review the book is written on a high scientific level, good language and will be of great interest not only for geographers, but also for international economists and political scientists.